Experimental results on the role of sheathing-to-frame and base connections of a European timber framed shear wall. (1st April 2015) - Germano, Federica; Metelli, Giovanni; Giuriani, Ezio
Highlights: The nail's surface feature affected the mechanical properties of the connections. The vertical load did not influence the behavior of the full-scale shear walls. The shear walls failed at 2.5% drift due to the low cycle fatigue fracture of nails. The contribution of each connection to the wall's total displacement was evaluated. The sheathing-to-frame connections dissipated more than 80% of the total energy. Abstract: In platform timber frame buildings the horizontal forces (wind, earthquake) are carried by the shear walls, whose hysteretic behavior is mainly governed by the sheathing-to-frame connections, if hold-downs and shear angle brackets at the wall base are designed with an adequate overstrength. The paper presents the experimental results obtained from tests both on connections between the sheathing panel and a timber stud and on full-scale prefabricated timber frame shear walls, with or without vertical loads. The results of monotonic and cyclic tests on nailed and stapled connections showed the importance of the surface feature of nails on initial stiffness and ductility of the connection. The full scale tests evidenced that the vertical load did not significantly influence the behavior of the walls, whose hysteretic response depended on the sheathing-to-frame connections which were able to dissipate more than 80% of the total energy. Furthermore, a dissipative hysteretic behavior of the shear wall was guaranteed up to 2.0% drift with the collapse governed by the low cycle fatigue failure of the steel nailed connections.